The performance of porous asphalt by using modified binder / Muhammad Mohktar Samat, Meor Othman Hamzah and Norizah Omar - Samat, Muhammad Mohktar; Hamzah, Meor Othman; Omar, Norizah (2008)
The application of porous asphalt on traffic safety grounds in Malaysia is relatively new. Encouragement on use of porous asphalt to mitigate road accidents has been spelt out in a Highway Planning Unit report to the Economic Planning Unit (HPU, 1998). However, it is generally accepted that porous asphalt is not as long-lasting as asphaltic concrete. This paper present the result of a laboratory investigation to evaluate performance of porous mixes by using Styrene Butadiene Styrene (SBS) modified mixes compared to conventional 60/70 pen bitumen. Samples using these binder were prepared in the form of Marshall specimen. The specimens are then subjected to a series of performance testing. The results indicate an improvement in mix properties with SBS modified mixes.